Better than vegan : 101 favorite low-fat, plant-based recipes that helped me lose over 200 pounds - Sroufe, Del (BenBella Books, 2013)
"Eating healthy just got a whole lot easier. The science is very clear. A whole-foods, plant-based diet is the healthiest possible way to eat-but veganism itself doesn't mean health, as Chef Del Sroufe, author of the New York Times bestseller Forks Over Knives-The Cookbook, knows better than anyone. Sroufe managed to reach 475 pounds while eating a vegan diet rich in pastries, peanut butter, and potato chips. After converting to a vegan diet with minimal processed foods, sugars and added oils, he lost more than 240 pounds without giving up great food. In Better than Vegan, Sroufe provides more than a hundred recipes that prove that the healthiest diet can also be the most delicious." --